High-Resolution Trophic Models Reveal Structure and Function of a Northeast Pacific Ecosystem - Surma, Szymon; Christensen, Villy; Kumar, Rajeev; Ainsworth, Cameron H.; Pitcher, Tony J. (Frontiers in Marine Science, 2019)
This paper examines the structure and dynamics of the marine ecosystem surrounding Haida Gwaii (an archipelago in the southeastern Gulf of Alaska). Based on previous research, a set of improved mass-balanced models was constructed in Ecopath with Ecosim (EwE) to represent ecosystem states existing circa 1900, 1950, and currently. These models feature increased taxonomic and ecological resolution relative to their predecessors across trophic levels and size classes from zooplankton to whales. A more detailed representation of Pacific herring (Clupea pallasii), including its age structure, predators, and prey, was introduced to permit modeling of the ecosystem role of herring as a forage fish, as well as the ecological impacts of herring fisheries. Gross ecosystem structure and herring trophodynamics were compared across ecosystem states using size spectra and ecological indicators, including mixed trophic impacts. The 1950 model was fitted to a comprehensive set of biomass and catch time series. Dynamic ecosystem simulations evaluated the influence of fishing, predation, other natural mortality, and primary productivity trends on ecosystem behavior since 1950, as well as the relative importance of top-down versus bottom-up forcing. Size spectra and ecosystem indicators suggest that the Haida Gwaii ecosystem has not undergone a radical structural shift since 1900, despite heavy exploitation of numerous marine mammals and fish. Moreover, mixed trophic impacts show that herring constitutes an important mid-trophic level node in the food web, participating in complex interactions with many predators, prey, and competitors. Dynamic ecosystem simulations demonstrate that trends in fishing mortality, trophic interactions, and primary productivity (correlated with the Pacific Decadal Oscillation) are all necessary to explain historical Haida Gwaii ecosystem behavior. These interacting drivers yield a mosaic of top-down and bottom-up trophic control for trophic interactions involving herring and throughout the food web. Simulation results also suggest that production of several herring, salmon, and groundfish stocks may have recently become partially decoupled from primary productivity, perhaps due to changes in copepod guild composition. These results also indicate that a biodiversity decline and “fishing down the food web” occurred off Haida Gwaii since 1950. Finally, the fitted 1950 model provides a robust platform for dynamic ecosystem simulations.